The Global Outbreak Alert and Response Network - Mackenzie, John; Drury, P.; Arthur, R.; Ryan, M.; Grein, T.; Slattery, R.; Suri, S.; Domingo, C.; Bejtullahu, A. (Routledge, 2014)
The Global Outbreak Alert and Response Network (GOARN) was established in 2000 as a network of technical institutions, research institutes, universities, international health organisations and technical networks willing to contribute and participate in internationally coordinated responses to infectious disease outbreaks. It reflected a recognition of the need to strengthen and coordinate rapid mobilisation of experts in responding to international outbreaks and to overcome the sometimes chaotic and fragmented operations characterising previous responses. The network partners agreed that the World Health Organization would coordinate the network and provide a secretariat, which would also function as the operational support team. The network has evolved to comprise 153 institutions/technical partners and 37 additional networks, the latter encompassing a further 355 members and has been directly involved in 137 missions to 79 countries, territories or areas. Future challenges will include supporting countries to achieve the capacity to detect and respond to outbreaks of international concern, as required by the International Health Regulations (2005). GOARN's increasing regional focus and expanding geographic composition will be central to meeting these challenges. The paper summarises some of network's achievements over the past 13 years and presents some of the future challenges.